2013
DOI: 10.1590/s0034-737x2013000300014
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency and response of conilon coffee clones to phosphorus fertilization

Abstract: Studies on nutritional efficiency of phosphorus in conilon coffee plants are important tools to unravel the high limitation that natural low levels of this nutrient in soil impose to these species cultivars. Therefore, this study aimed at evaluating the nutritional efficiency and the response to phosphorus of conilon coffee clones. Plants were managed during 150 days in pots containing 10 dm³ of soil, in greenhouse. A factorial scheme 13 x 2 was used, with three replications, being the factors: 13 clones const… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(28 citation statements)
references
References 15 publications
1
27
0
Order By: Relevance
“…The nutritional content in plant tissues; the efficiency in which the plants acquire, translocate and utilize the nutrients; and tolerance to cultivation in environment with low fertility have all been successfully used as parameters to study the variability among genotypes of C. canephora and to identify groups with different traits (Martins et al, 2013a;2013b;Colodetti et al, 2014;Machado et al, 2016;Martins et al, 2015b;Starling et al, 2018). Differences among genotypes were observed for the content of all macronutrients in green tissues, and the magnitude of the genetic parameters showed that nutritional contents can be greatly influenced by the genetic constitution (Table 1).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The nutritional content in plant tissues; the efficiency in which the plants acquire, translocate and utilize the nutrients; and tolerance to cultivation in environment with low fertility have all been successfully used as parameters to study the variability among genotypes of C. canephora and to identify groups with different traits (Martins et al, 2013a;2013b;Colodetti et al, 2014;Machado et al, 2016;Martins et al, 2015b;Starling et al, 2018). Differences among genotypes were observed for the content of all macronutrients in green tissues, and the magnitude of the genetic parameters showed that nutritional contents can be greatly influenced by the genetic constitution (Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…Clonal cultivars are composed of a group of genotypes that may present different nutritional demands or efficiencies, as well as different tolerances to nutritional stresses. Differences in the nutritional efficiency among genotypes of Coffea canephora have been reported for several nutritional parameters (Martins et al, 2013a;Colodetti et al, 2014;Machado et al, 2016;Martins et al, 2015a).…”
Section: Introductionmentioning
confidence: 99%
“…Contrarily, genotype 32 has reduced capacity to accumulate P when grown in environments with low availability of this nutrient; however, this genotype can increase the accumulation of P up to 700% when the nutrient supply increases, in contrast to only 310% achieved by genotype 24 (Martins et al, 2013b). This finding implies that the capacity to discriminate genotypes for tolerance may be strongly connected to the nutritional efficiency expressed by the genotypes, particularly the efficiency to utilize P from the soil.…”
Section: Differential Tolerance To An Environment With Restricted Phomentioning
confidence: 95%
“…The factors were 13 genotypes of Conilon coffee divided into three groups based on differences in the ripening cycle, and three environments with different levels of P availability in the soil: fertilization without P supply, and P supply at 50 and 100% of the recommended level (see Martins et al, 2013b).…”
Section: Experimental Design and Conduct Of The Studymentioning
confidence: 99%
See 1 more Smart Citation